The impact of hypoglycaemia on the quality of life of family members of adults with type 1 or type 2 diabetes: A qualitative systematic review. Issue 10 (6th August 2021) - Jensen, Mette Valdersdorf; Broadley, Melanie; Speight, Jane; Scope, Alison; Preston, Louise; Heller, Simon; de Galan, Bastiaan E.; Pouwer, Frans; Hendrieckx, Christel; ,
Abstract: Aim: To summarize and critically appraise the recent qualitative evidence regarding the impact of hypoglycaemia on the quality of life of family members of adults with type 1 or type 2 diabetes. Methods: Four databases were searched systematically (MEDLINE, PsycINFO, CINAHL and Cochrane Library), and results were screened for eligibility. Article quality was assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Qualitative Research. Data were extracted, coded and analysed using thematic analysis. The systematic review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) and Enhancing transparency in reporting of qualitative research (ENTREQ) guidelines. Results: Eight qualitative studies were included in the final review. The majority of participants were partners or spouses of adults with type 1 diabetes. Thematic synthesis resulted in six analytical themes: 'Hypoglycaemia alters everyday life, reducing freedoms and increasing disruptions', 'Hypoglycaemia has an adverse impact on sleep', 'Hypoglycaemia negatively changes the relationship with the person with diabetes', 'Hypoglycaemia negatively impacts emotional well‐being', 'The detection, prevention, and treatment of hypoglycaemia consumes time and energy' and 'Family members have unmet needs for informational and emotional support regarding hypoglycaemia'. Across the six analytical themes, family members described how hypoglycaemia has a severe negative impact on different aspects of their lives, including daily living, personal relationships and emotional well‐being. Conclusions: Family members experience the impact of hypoglycaemia as a major recurrent challenge in their lives. The unmet needs of family members need further attention in research and clinical practice.